The Improvement of Creativity through Problem-Based Learning in Social Science for Elementary School Students - Eka Suryanti (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
This study aims to improve the creativity of fourth grade students in social science learning through the Problem Based Learning (PBL) model at SDN 18 Pontianak. The type of research was Classroom Action Research, with the research subjects of fourth grade students of SDN 18 West Pontianak totaling 31 students. The methods used to collect data were test and observation. The data analysis technique used was descriptive quantitative. The success criteria used in this study were an increase in creativity which is characterized by an increase in fluency of thinking, flexibility of thinking, sensitivity, originality of thinking, ability to detail, inquisitive attitude, courage to take risks, not easily discouraged, interested in compound tasks, appreciative attitude and 75% of the number of students have achieved a creativity score of ≥76% then the action is declared successful. The results showed that the implementation of the PBL model in social science subjects can increase student creativity in social science learning. Increased creativity in fourth grade students of SDN 18 Pontianak through the process of orienting students to the problem, organizing students to learn, guiding individual and group experiences, helping students develop and present work, analyzing and evaluating the problem solving process. This was indicated by an increase in student creativity in social science learning after being subjected to action in cycle I obtained student scores when the pre-test showed 24 students (77.42%) in the low category and 7 students (22.58%) in the medium category. Scores in post-test I showed 13 students (41.93%) in the medium category and 18 students (58.07%) in the low category, and the acquisition of post-test II scores showed 31 students (100%) in the high category. The increase occurred in cycle I as many as 5 students (16.12%)increased from the low category to medium and the increase in cycle II showed 31 students (100%) increased to the high category with the score having met 75% of the number of students achieving a score of ≥76%.